Hommes et natures. People and natures. Seres humanos y naturalezas - Motte-Florac, Elisabeth (Focus, 2012)
Understanding how human societies and their natural environment mutually influence each other is at the heart of current major environmental issues, including sustainable development and climate change. Indigenous peoples and local communities -holders of a rich knowledge about nature and related technical know-how- are fully recognized as key actors in policies pertaining to biodiversity management. The photographs presented in this book reveal the impressive complexity of linkages woven over time between people and natures, on all continents and in the most diverse environments. They also show the diverse related ways of life and the wide array of subjects that need to be explored in order to decrypt such complexity.